2013
DOI: 10.1021/ed3005903
|View full text |Cite
|
Sign up to set email alerts
|

Seeing Chemistry through the Eyes of the Blind: A Case Study Examining Multiple Gas Law Representations

Abstract: Adequately accommodating students who are blind or low-vision (BLV) in the sciences has been a focus of recent inquiry, but much of the research to date has addressed broad accommodations rather than devising and testing specific teaching strategies that respond to the unique challenges of BLV students learning chemistry. This case study seeks to identify instructional techniques that support or impede the representation of information for BLV students in the context of a typical gas laws unit in a college che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 9 publications
0
43
0
4
Order By: Relevance
“…However, research should also focus on how such tools are used by a variety of students. For example, Harshman, Bretz, and Yeziersk found that accommodations produced by sighted researchers could be overwhelming for learners who are blind or who have low vision [63]. Thus, future work should investigate alternate representations of information and how these alternatives are used by a variety of students.…”
Section: Future Workmentioning
confidence: 99%
“…However, research should also focus on how such tools are used by a variety of students. For example, Harshman, Bretz, and Yeziersk found that accommodations produced by sighted researchers could be overwhelming for learners who are blind or who have low vision [63]. Thus, future work should investigate alternate representations of information and how these alternatives are used by a variety of students.…”
Section: Future Workmentioning
confidence: 99%
“…However, some researchers may choose to use unstructured interviews to gather information that can help them develop more structured interview protocols to use in their data collection. One interesting use of an unstructured interview in CER is a recent study designed to identify effective instructional strategies for assisting a visually impaired student in understanding gas laws (6). The researchers used tutoring sessions as an initial data source.…”
Section: Unstructured Interviewsmentioning
confidence: 99%
“…The use of this type of software can help chemistry education researchers more easily identify trends in students' alternative conceptions (18), explore teachers' instructional goals and strategies (19,20), collect exploratory data to guide the development of quantitative research instruments (21), identify educational approaches that support learning (22), or elicit students' beliefs and perspective about diverse educational issues (23). The default structure of the coding scheme in common CAQDAS packages tends to be hierarchical (except in ATLAS.ti).…”
Section: Coding Of Datamentioning
confidence: 99%